Green chemistry approach for preparation of hydrogels for agriculture applications through modification of natural polymers and investigating their swelling properties - Manar Elsayed Abdel-Raouf; Shimaa Mohmaed El-Saeed; Elsayed Gamal Zaki; Ahmed Mohamed Al-Sabagh (Egyptian Journal of Petroleum)
Two sets of hydrogel materials based on guar gum were prepared by grafting guar gum onto acrylic acid/acrylamide and acrylic acid/N-isopropylacrylamide copolymers by using persulphate radical as an initiator and N,N′ methylenebisacrylamide as a cross linker. The prepared hydrogels were denoted as AA-AcM-GG and AA-NIPAM-GG respectively. They were characterized by FTIR Spectroscopy and SEM. The effect of some composition variables on the swelling performance of PA-GG hydrogel was thoroughly studied. Furthermore, swelling behavior was monitored as a function of temperature and electrolyte concentration. A lab experiment was carried out in order to investigate the effect of the optimum hydrogels on the growth of guava plant. Keywords: Guar gum, Acrylate, N-isopropyl acryl amide, Green hydrogels, Temperature sensitive, Salt sensitive